Changes in Cave Sedimentation Mechanisms During the Late Quaternary: An Example From the Lower Cerovačka Cave, Croatia - Kurečić, Tomislav; Bočić, Neven; Wacha, Lara; Bakrač, Koraljka; Grizelj, Anita; Tresić Pavičić, Dinko; Lüthgens, Christopher; Sironić, Andreja; Radović, Siniša; Redovniković, Loris; Fiebig, Markus (Frontiers in Earth Science, 2021)
During archeological excavations in the Lower Cerovačka Cave (Mt. Velebit, Croatia), the test trench penetrated to a depth of 1.8 m. An undisturbed sequence of sediments was exposed. Considering that caves represent highly efficient sediment traps it was possible to recognize changes in the depositional mechanisms during the Pleistocene-Holocene period. Using the multiproxy approach, the mineralogical, petrographic, and biostratigraphic characterization of the cave sediments was performed. Facies analysis revealed several stages in the development of the clastic filling of cave channels. Allochthonous origin of the sediment was assumed. Sedimentation took place under various conditions from pronounced cold and dry climate during Pleistocene stages in the base of the profile, to humid periods with anthropogenic influence during the Holocene at the very top of the profile. Although traditionally these sediments were believed to be of a Pleistocene age, here for the first time a stratigraphic calibration of the profile has been performed based on luminescence dating of detrital cave sediments and radiometric dating of speleothems.